Fabrication, mechanical properties, and tribological behaviors of Ti2AlC and Ti2AlSn0.2C solid solutions - Leping Cai; Zhenying Huang; Wenqiang Hu; Suming Hao; Hongxiang Zhai; Yang Zhou (Journal of Advanced Ceramics, 2017)
Abstract Highly pure and dense Ti2AlC and Ti2AlSn0.2C bulks were prepared by hot pressing with molar ratios of 1:1.1:0.9 and 1:0.9:0.2:0.85, respectively, at 1450 °C for 30 min with 28 MPa in Ar atmosphere. The phase compositions were investigated by X-ray diffraction (XRD); the surface morphology and topography of the crystal grains were also analyzed by scanning electron microscopy (SEM). The flexural strengths of Ti2AlC and Ti2AlSn0.2C have been measured as 430 and 410 MPa, respectively. Both Vickers hardness decreased slowly as the load increased. The tribological behavior was investigated by dry sliding a low-carbon steel under normal load of 20–80 N and sliding speed of 10–30 m/s. Ti2AlC bulk has a friction coefficient of 0.3–0.45 and a wear rate of (1.64–2.97)×10−6 mm3/(N·m), while Ti2AlSn0.2C bulk has a friction coefficient of 0.25–0.35 and a wear rate of (2.5–4.31)×10−6 mm3/(N·m). The influences of Sn incorporation on the microstructure and properties of Ti2AlC have also been discussed.